(untitled) (Medico Legal Update, 2021)
Optical biosensors present great characteristics compared to traditional analytical techniques because they allow direct, realistic, and label-free detection of many biological and chemical materials. Thyroid hormones are created by the thyroid gland, which is found in the abdomen of the thyroid cartilage Thyroid hormone governs metabolic processes necessary for normal outgrowth and evolution in addition to regulating metabolism in adults. It is established that the condition of the thyroid hormone is related to body weight and energy disbursement. This work using a single-mode tapered fiber biosensor to detect changes in the level of thyroid hormone by measurement of the intensity changing with the concentration of hormone by using a diode laser (450 nm) wavelength as an optical source, the single-mode tapered fiber as the sensor connected with ocean (HR 2000) spectrum analyzer by an adapter and finally connected to the pc to show the result. The lowest intensity of transmitted light recorded with a higher concentration of the hormone because of the high matching and specific selection of laser wavelength with the structure of the thyroid hormone in which give the specific amount of the hormone present in the sample. Thyroid hormone can be detected by using a laser biosensor. The higher concentration of thyroid hormone referred to the lowest intensity of light.